Introduction - Beaupré, R. (Les Cahiers de droit, 1984)
A comparative study of the interpretative methodology applicable in multilingual jurisdictions such as Canada, Belgium and Switzerland and before the Court of Justice of the European Communities reveals some remarkable similarities as well as some important differences. The four papers that follow were presented during a seminar on the theme « Interpretation of Multilingual Statutes and Treaties » that was held in Strasbourg on July 10, 1984 under the auspices of the Canadian Institute for Advanced Legal Studies. The Canadian author of one of the papers also served as rapporteur for the seminar. His report serves as an introduction to the four papers.